Silver nanoparticles synthesized by thermal reduction of a silver(I)-aspartame complex in inert atmosphere - Cavicchioli, M.; Varanda, L. C.; Massabni, Antonio Carlos [UNESP]; Melnikov, P. (Elsevier B.V., 2005)
Synthesis of silver nanoparticles by thermal treatment of a silver-aspartarne complex under inert atmosphere is described. Spherical metallic silver naroparticles with average diameter of 5 +/-2 nm were obtained by thermal treatment of the complex [Ag(C14H17N2O5)] 1/2H(2)O at 185 degrees C. Thermogravimetric and infrared analysis of the product show the occurrence of an ester bond cleavage of the aspartame ligand followed by rearrangement and release of a molecule of formaldehyde (H2CO), which is transformed in two strong reducing molecules, H-2 and CO. For silver reduction, the presence of the formaldehyde molecules seems to be the key process for the metallic nanoparticles fort-nation. The maintenance of the ligand crystalline structure, with the exception of the ester group loss, was noted as essential for nanoparticles formation and size control. The ligand crystalline structure was completely lost at 200 degrees C and particle growth and coalescence were observed above 250 degrees C. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: nanomaterials; heat treatment; characterization methods; silver-aspartame complex